Dharmagita Dalam Pelaksanaan Upacara Yajña Di Kecamatan Tegallalang Kabupaten Gianyar: (Kajian Filsafat Hindu) - Piartha, I Nyoman (Jurnal Penelitian Agama Hindu, 2024)
Dharmagita in the religious and social life of Hindus is a form of offering sound art as a form of offering. Dharmagita is always present in Hindu religious ceremonies in Tegallalang District, giving the impression that the dharmagita accompanies the yajña. This research aims to examine the use of dharmagita in the yajña ceremony in Tegallalang sub-district, Gianyar district, and to discover the elements of Hindu philosophy contained in dharmagita. In general, this research aims to explore and provide a clear understanding of dharmagita and its use in yajña ceremony in Tegallalang District, Gianyar Regency, Hindu philosophy studies. This research uses three theories, functional structural theory, religious theory, and symbol theory to examine the dharmagita problem in Tegallalang district. This research is qualitative research with a phenomenological approach, which took the research location in the tegallalang sub-district, because it is seen from the phenomenon of socio-religious life in communities located in the transition area between sub-district and rural areas. The data sources in this research use primary data sources and secondary data sources. The results of this research confirm that dharmagita is a form of sound art offered to God in the yajña ceremony, including the god yajña, butha yajña, manusa yajña, pitra yajña, and rsi yajña ceremonies. Hindu philosophy in the dharmagita includes tattwa teachings which emphasize the divine aspect and have implications for increasing the sraddha and bhakti of the people in the yajña ritual.